A Case Study: Reading Strategies Training Scheme in a Hong Kong Primary School. Issue 1 (20th August 2016) - Lee, Ho Cheung
Abstract : This article describes a case study on a reading programme, named Reading Strategies Training Scheme (RSTS), for second language learning in a Hong Kong primary (elementary) school. The scheme, serving learners of English as a second language from Primary One to Six (ages 6–12), was developed by the school's English teaching team. As it was being implemented, the teachers noticed the effectiveness of teaching reading strategies explicitly and of the scheme's role in their professional growth. This article examines the impact of RSTS after its first year, discusses the significance of collaborative work among frontline educators, and gives suggestions as to how a skill‐oriented reading programme could be constructed in a teaching community.